KARAKTERISTIK PENDERITA GAGAL GINJAL KRONIK YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015-2016 - Yossi Sepriani Purba; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Chronic Renal Failure (CRF) is condition of disfunctioned kidney and unable to filter blood as well as healthy kidney. According to Center for Chronic Disease Prevention and Health Promotion (CDC),CRF is the ninth rank of death cause in America. About 1 of 2 adults of 30-64 years old is in risk of CRF (WHO, 2015).The result of Basic Health Reasearch (2013) indicated that the highest prevalence of  CRF patient is in ≥75 years 0,6 %. This research is descriptive with case series design which aims to identify the characteristics of CRF patient hospitalized in Santa Elisabeth Medan Hospital in 2015-2016. Population size is also the sample size which are 106 patient's medical records. Univariate data is analysed descriptively and bivariate by Chi Square and Kruskal Wallis test. Highest proportion of CRF patient are in 54-63 years old (31,2%), man (52,8%), Christian (62,3%), Bataknese (86,9%), entrepreneur (31,3%), outside Medan (54,7%), more than 1 main complaint (53,8%), more than 1 disease history (29,2%), average length of stay 6,20 days, non self cost (74,5%), blood ureum level >39mg/100ml (94,4%), blood creatinin level >1.5mg/100ml (96,3%), haemoglobin level <12gr/dl (93,4%), 5th stadium (70,8%), drugs with diet and hemodialysis (66,0%), becoming outpatient (76,4%). There is significant difference in proportion of average length of stay based on CRF stadium. It is recommended to everyone to keep your kidney healthy by keep healthy life style.For Santa Elisabeth Medan Hospital to complete record of condition when being out of hospital, blood ureum and creatinin level record, haemoglobin level record, and CRF stadium record. For other researcher to conduct further analytical research. Keywords: CKF, patient's characteristics, case series